Models of constitutional justice in comparative perspective: Mexico– Colombia– Argentina - Valles Santillán, Gabriela Guadalupe (2025)
This article will present the essential features of constitutional review process in each of the following three Latin American countries: Mexico, Colombia and Argentina. The intention is to make an intersectional analysis and identify the mechanisms each country uses to resolve inconsistencies between supreme norm and secondary legislation in jurisdictional proceedings, and then to identify common solutions to practical problems that the three legal systems present in this regard. This analysis is based on the premise that the aforementioned countries share legal, political, social, and cultural elements that can be resolved through the argumentative tools of constitutional jurisdiction. The methodology used in this reflective article will be a literature review and comparative legal analysis. It is evident that the three countries have opted for constitutional control mechanisms that seek to safeguard the supremacy of the Constitution and the effective protection of rights. However, procedural complexity and the coexistence of concentrated and diffuse models mean that their models require clear strategies and an integrative vision.